Well-being as a Phenomenon: Research Paradigms of the Fifth Age; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Loyko O. T. Olga Timofeevna; Dementeva S. V. Svetlana Valerevna; Alexandrova M. A. Mariya Aleksandrovna; Mashkina O. Olga; Zeremskaya Yu. A. Yuliya Aleksandrovna (2017, 2017)
Title screen